Comparative Evolutionary Histories of the Fungal Chitinase Gene Family Reveal Non-Random Size Expansions and Contractions due to Adaptive Natural Selection - Magnus Karlsson; Jan Stenlid (Evolutionary Bioinformatics, 2008)
Gene duplication and loss play an important role in the evolution of novel functions and for shaping an organism's gene content. Recently, it was suggested that stress-related genes frequently are exposed to duplications and losses, while growth-related genes show selection against change in copy number. The fungal chitinase gene family constitutes an interesting case study of gene duplication and loss, as their biological roles include growth and development as well as more stress-responsive functions. We used genome sequence data to analyze the size of the chitinase gene family in different fungal taxa, which range from 1 in Batrachochytrium dendrobatidis and Schizosaccharomyces pombe to 20 in Hypocrea jecorina and Emericella nidulans , and to infer their phylogenetic relationships. Novel chitinase subgroups are identified and their phylogenetic relationships with previously known chitinases are discussed. We also employ a stochastic birth and death model to show that the fungal chitinase gene family indeed evolves non-randomly, and we identify six fungal lineages where larger-than-expected expansions (Pezizomycotina, H. jecorina, Gibberella zeae, Uncinocarpus reesii, E. nidulans and Rhizopus oryzae ), and two contractions ( Coccidioides immitis and S. pombe ) potentially indicate the action of adaptive natural selection. The results indicate that antagonistic fungal-fungal interactions are an important process for soil borne ascomycetes, but not for fungal species that are pathogenic in humans. Unicellular growth is correlated with a reduction of chitinase gene copy numbers which emphasizes the requirement of the combined action of several chitinases for filamentous growth.